Probing the Diversity of Polycomb and Trithorax Proteins in Cultured and Environmentally Sampled Microalgae - Zhao, Xue; Deton Cabanillas, Anne Flore; Veluchamy, Alaguraj; Bowler, Chris; Vieira, Fabio Rocha Jimenez; Tirichine, Leila (Frontiers in Marine Science, 2020)
Polycomb (PcG) and Trithorax (TrxG) complexes are two evolutionarily conserved epigenetic regulatory components that act antagonistically to regulate the expression of genes involved in cell differentiation and development in multicellular organisms. The absence of PcG in both yeast models Saccharomyces cerevisiae and Schizosaccharomyces pombe suggested that polycomb proteins might have evolved together with the emergence of multicellular organisms. However, high throughput sequencing of several microalgal genomes and transcriptomes reveals an unprecedented abundance and diversity of genes encoding the components of these complexes. We report here the diversity of genes encoding PcG and TrxG proteins in microalgae from the Marine Microbial Eukaryote Transcriptome Sequencing Project database (MMETSP) and detected at broad scale in Tara Oceans genomics datasets using a highly sensitive method called eDAF (enhanced Domain Architecture Filtering). Further, we explored the correlation between environmental factors measured during the Tara Oceans expedition and transcript levels of PcG and TrxG components. PcG and TrxG are responsible for the deposition of a number of histone marks among which a TrxG associated mark, H3K4me3 which we profiled genome wide in the model diatom Phaeodactylum tricornutum to understand its role in microalgae and revisited the previously published histone code and co-occurrence with other histone marks including the antagonizing Polycomb deposited mark H3K27me3.